Terror in the heart of freedom : citizenship, sexual violence, and the meaning of race in the postemancipation South - Rosen, Hannah (Hannah R.) (Gender & American culture., 2009)
The meaning of race in the antebellum southern United States was anchored in the racial exclusivity of slavery (coded as black) and full citizenship (coded as white as well as male). These traditional definitions of race were radically disrupted after emancipation, when citizenship was granted to all persons born in the United States and suffrage was extended to all men. Hannah Rosen persuasively argues that in this critical moment of Reconstruction, contests over the future meaning of race were often fought on the terrain of gender. Sexual violence--specifically, white-on-black rape--emerged as.